WORK LIFE BALANCE, ORGANIZATIONAL CITIZENSHIP AND ORGANIZATIONAL COMMITMENT: STUDY FROM BANKING INDUSTRY EMPLOYEE - Margaretha, Meily; Sinuraya, Candra (International Journal of Psychosocial Rehabilitation, 2020)
Work life balance defined as the ability of individuals to fulfill work and family responsibilities and other non-work responsibilities. With this balance it is possible for someone to have a life that meets their goals. Organizational citizenship behavior refers is the behavior of employees towards the company without coercion or compensation for the services employees provide to the company.Organizational commitment is one of the attitudes of employees who describe the feelings of like or dislike towards the organization where employees work. The aim of this study is to investigate variable of work life balance influence employee organizational citizenship behavior and organizational commitment. The primary data came from 178 sample size selected by using survey questionnaire from a number of employees who work at banking industry in city of Bandung, Indonesia. Data analyzed through confirmatory factor analysis technique and regression analysis. The outcomes of the study showed that relationship between work life balance and organization citizenship behavior have no direct effect on organizational citizenship behavior, meanwhile work life balance has a significant effect on employee organizational commitment. This research will enrich the discourse on the relationship between work life balance toward organizational citizenship behavior and organizational commitment. The study has suggested implications for researchers, practitioners, and experts in the field of human resource management.